2003
DOI: 10.1093/humrep/deg037
|View full text |Cite
|
Sign up to set email alerts
|

17 -Estradiol and environmental estrogens significantly affect mammalian sperm function

Abstract: This study provides the first evidence that E(2) and environmental estrogens can significantly stimulate mammalian sperm capacitation, acrosome reactions and fertilizing ability, with the environmental estrogens being much more potent than E(2). The inability of hydroxytamoxifen to block these responses suggests that classical estrogen receptors may not be involved. Whether these responses have effects on fertility in vivo remains to be determined, along with the mechanisms of action involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
120
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 40 publications
10
120
2
2
Order By: Relevance
“…These data are consistent with the results of the western blot analysis, where a reduced expression of both AR isoforms was observed, and with recent data reported by Zalata et al (2013). A functional role for steroid receptors in capacitation, acrosome reaction, motility, and survival in sperm has been reported (Adeoya-Osiguwa et al 2003). It is well known that human ejaculated sperm are not capable of fertilizing oocyte as they need two important sequential steps: capacitation and acrosome reaction.…”
Section: Discussionsupporting
confidence: 92%
“…These data are consistent with the results of the western blot analysis, where a reduced expression of both AR isoforms was observed, and with recent data reported by Zalata et al (2013). A functional role for steroid receptors in capacitation, acrosome reaction, motility, and survival in sperm has been reported (Adeoya-Osiguwa et al 2003). It is well known that human ejaculated sperm are not capable of fertilizing oocyte as they need two important sequential steps: capacitation and acrosome reaction.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the concentration of estrogen in ovarian fluid is much higher when compared with the plasma (Free & Jaffe 1979, Hess et al 1995 and it reaches multiple values depending on the time of the estrus fluctuating between 145 and 2100 pg/ml in rats and mice (Shaikh 1971). Most of our knowledge regarding these processes has been obtained from in vitro studies (Adeoya-Osiguwa et al 2003, Ded et al 2010, Sebkova et al 2012, and for this reason it is really important to also do in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated previously that oestradiol increased motility, oxidative metabolism, longevity of spermatozoa and oocyte penetration (Idaomar et al 1989). Recently, it has been shown that oestradiol and phytoestrogens improve mouse sperm capacitation (Adeoya-Osiguwa et al 2003). Thus oestrogens may act via a membrane oestrogen-binding protein, to exert a rapid effect.…”
Section: Discussionmentioning
confidence: 98%